2011
DOI: 10.1096/fj.10-167684
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin is required for postmitotic Golgi reassembly

Abstract: During the G2-M transition, the highly organized Golgi apparatus undergoes reversible fragmentation through unstacking of the cisternal ribbon and disassembly into radially dispersed vesicles and tubules. These Golgi-derived fragments redistribute randomly within the cytoplasm, partition stochastically, and in telophase coalesce to generate a functionally and structurally intact Golgi complex. Here we identified a novel step in postmitotic Golgi reassembly that requires the clathrin heavy chain (CHC). We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, like in other eukaryotes CHC1 appears to be involved in segregation of the Golgi during mitosis [36]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, like in other eukaryotes CHC1 appears to be involved in segregation of the Golgi during mitosis [36]. …”
Section: Resultsmentioning
confidence: 99%
“…Over the last 50 years a growing number of functional studies have reported evidence for its impact on diverse physiologically processes besides its role in endocytic and secretory membrane transport, such as cytokinesis [8,39,40], Golgi integrity [36], secretory granule biogenesis [41], and mitotic and meiotic spindle organisation and stabilisation [42,43]. Without exception clathrin localisation was always correlated with its site of action in these reports.…”
Section: Discussionmentioning
confidence: 96%
“…There are multiple well-defined roles for clathrin in the TGN, ranging from sorting lysosomal enzymes to contributing to maturation of secretory granules by removal of constitutively expressed proteins (Figure 1) (Brodsky et al 2001 after drug-induced fragmentation (Radulescu et al 2007) and fragmentation during mitosis (Radulescu & Shields 2012). This may be the result of a requirement for clathrin-mediated membrane traffic to deliver needed proteins that mediate Golgi-stack fusion.…”
Section: Trans-golgi Network and Golgi Functions Of Clathrinmentioning
confidence: 99%
“…Both dystonin-a2 and MACF1b have been found in the Golgi apparatus, and overexpressed dystonin-a2 colocalizes with the cis -Golgi protein GM130, suggesting a functional role in Golgi apparatus-mediated MT nucleation [ 119 , 136 , 142 ]. Other MT-associated proteins, such as MAP1B and clathrin, have been shown to promote MT polymerization and stability when localized to the Golgi apparatus [ 143 , 144 ]. Dystonin-a2 has been shown to interact with both MAP1B and clathrin via the modular plakin domain [ 145 ].…”
Section: Dystonin and The Plakin Family Of Cytoskeletal Linker Promentioning
confidence: 99%